KLASIFIKASI PEMANFAATAN OPEN SOURCE RESOURCE PADA MULTI-EDGE COMPUTING DENGAN JARINGAN PRIVATE 5G YANG BERKUALITAS DAN LOW LATENCY MENGGUNAKAN TEKNOLOGI NETWORK SLICING - Oka Prasetiyo; Yuma Akbar (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Multi-edge computing is one of the technologies that allows data processing to be performed at the edge of the network, thereby reducing latency and speeding up overall data processing. On the other hand, 5G private networks with high quality and low latency enable fast and stable data transmission. However, in implementing multi-edge computing technology with 5G private networks, it is necessary to use the right open source resources to support its success at a lower investment cost. This thesis aims to classify the utilization of open source resources in multi-edge computing technology with quality and low latency 5G private networks using network slicing technology. The development methodology includes literature study, system development, data collection, data analysis, and system performance evaluation implemented on top of type 2 hypervisor virtualization on Virtualbox. The results of this thesis are expected to show that there are several open source resources that can be used in multi-edge computing technology with 5G private networks, such as Open5gs, Kubernetes, Virtualbox, so as to form a network with low latency and low cost.